2020
DOI: 10.1186/s12887-020-02200-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in two Polish neonates with alveolar capillary dysplasia

Abstract: Background: Alveolar capillary dysplasia (ACD) is a rare cause of severe pulmonary hypertension and respiratory failure in neonates. The onset of ACD is usually preceded by a short asymptomatic period. The condition is refractory to all available therapies as it irreversibly affects development of the capillary bed in the lungs. The diagnosis of ACD is based on histopathological evaluation of lung biopsy or autopsy tissue or genetic testing of FOXF1 on chromosome 16q24.1. Here, we describe the first two Polish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…6,7 Topical applications of a NO donor increase erythropoietin production in the kidney, 8 and inhalation of NO improves pulmonary hypertension in premature neonates. 9 In contrast, blockade of NO synthesis decreases T regulatory cells, worsens renal damage and increases blood pressure in rats. [10][11][12] Studies have also demonstrated an important regulatory role for NO in cutaneous functions.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Topical applications of a NO donor increase erythropoietin production in the kidney, 8 and inhalation of NO improves pulmonary hypertension in premature neonates. 9 In contrast, blockade of NO synthesis decreases T regulatory cells, worsens renal damage and increases blood pressure in rats. [10][11][12] Studies have also demonstrated an important regulatory role for NO in cutaneous functions.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the abnormal results of multi-system malformations of the fetus such as congenital cardiac, lung, genitourinary and gastrointestinal anomalies, the diagnoses of ACD/MPV and LDS of the fetus were further de ned. In addition to our fetus, table 1 shows another 10 patients with a different fragment deletion in the 16q24.1q24.2 region and complete information, and the fragment sizes range from 0.9 Mb to 3.5 Mb, containing FOXF1, FOXL1 and FOXC2 genes, among which, two fetuses were from de novo mutation, four patients from maternal heredity, four patients from unknown origin, three females and seven males are enrolled from ve literatures [3,[9][10][11][12]. As is shown, the deleted sizes of 16q24.1q24.2 fragment are not proportional to phenotype severity and both the cardiac and renal anomalies are the two major symptoms during the fetal period, while the phenotypes of our fetus are the most serious, showing the changes of cardiopulmonary structure such as pulmonary artery dilatation, HLHS, complete AVSD, CAV, FOC, ASD, VSD; the upper pyloric obstruction manifestations; a hypodense mass in the left kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, about 50 to 75 percent of affected newborns have multiple-system abnormalities such as hypoplastic left heart syndrome (HLHS), intestinal malrotation (IM) [2]. In approximately 80-90% of ACD/MPV patients, heterozygous single nucleotide variants (SNVs) or copy number variant (CNV) deletions involving forkhead box F1 (FOXF1, OMIM 601089) and / or forkhead box C2 (FOXC2, OMIM 602402) at chromosome 16q24.1 have been found [3,4]. In this report, we describe a fetus featured as a series of diverse structural malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, inhibition of iNOS activity alleviates damage to both the liver and the kidneys in bile duct-ligated rats [8]. Moreover, inhalation of NO improves lung function in both humans and animals [9][10][11]. Likewise, supplemental NO can improve tolerance to aerobic and anaerobic exercise in untrained or moderately trained humans [12].…”
Section: Introductionmentioning
confidence: 99%